Removal of Donor Human Leukocyte Antigen Class I Proteins With Papain. Issue 4 (April 2015) - Mera, Toshiyuki; Faustman, Denise L.
<x xml:space="preserve">Abstract</x> Background Papain is a protease with potential use in transplantation because of its targeted capacity to selectively remove human leukocyte antigen (HLA) class I proteins from donor human cells. However, its proteolytic activity has not been studied under conditions suitable for use in perfusing donor organs, namely, under a temperature of 4°C and dissolution in Belzer-UW solution. Methods We test papain's HLA class I removing activity under recognized whole organ transplant conditions of lowered temperature. The activity of papain's substrate selectivity was tested using both a test substrate (casein) and fresh peripheral blood lymphocytes (PBLs). The activity of papain was also tested at 4°C, the temperature of whole organ storage. Results We found that papain at a range of concentrations is nearly as active in cleaving the test substrate in Belzer-UW solution as in distilled water. In distilled water, papain is as active in cleaving a test substrate at a temperature of 4°C as compared to its optimal temperature of 37°C, if the incubation time is extended from 10 min to 3 hr. This finding also holds true if papain is dissolved in Belzer-UW solution. In peripheral blood lymphocytes, papain cleaved off HLA class I proteins as effectively at 4°C as at 37°C, provided the incubation time was also extended to 3 hr. Conclusion These findings suggest that papain's targeted enzymatic cleavage of donor HLA class I has potential use in the whole organ transplant setting with retained activity at lower temperatures and when activated and dissolved in Belzer-UW solution.